IDENTIFIKASI PENAMBAHAN SERBUK TEMBAGA PADA PELAT PENYERAP MORTAR UNTUK MENINGKATKAN KINERJA SOLAR WATER HEATER - Achmad Burhanudin; Nova Risdiyanto Ismail; Dadang Hermawan; Akhmad Farid (Mechanical Engineering Department, Faculty of Engineering, Universitas Lambung Mangkurat, 2025)
Indonesia has a high potential for solar energy, yet it is not optimally utilized. Additionally, the demand for hot water in Malang City is considerable. To meet this need, solar water heaters (SWH) can harness solar energy. However, one issue with SWH is that the mortar absorber plate has low thermal conductivity. This can be improved by adding copper powder to the mortar absorber plate. This study aims to identify the effects of adding copper powder to the absorber plate to enhance the performance of the solar water heater. The research compares mortar absorber plates with and without copper powder. Testing is conducted with varying flow rates. The study employs experimental methods, utilizing microscopic imaging, thermal conductivity tests, and SWH performance assessments. Microscopic analysis revealed that copper powder mixed with cement enhances the mortar. The addition of copper powder to the absorber plate (SWH.T) increases thermal conductivity by 25.16% compared to the standard version (SWH.S). Efficiency improvements for SWH.T over SWH.S at flow rates of 50, 150, and 250 ml/min are 24.20%, 9.91%, and 11.79%, respectively, with the highest efficiency for SWH.T at 250 ml/min reaching 45.56%.